2019
DOI: 10.1155/2019/8404035
|View full text |Cite
|
Sign up to set email alerts
|

Can We Identify or Exclude Extensive Axillary Nodal Involvement in Breast Cancer Patients Preoperatively?

Abstract: Background Breast cancer treatment has rapidly changed in the last few years. Particularly, treatment of patients with axillary nodal involvement has evolved after publication of several randomized clinical trials. Omitting axillary lymph node dissection in selected early breast cancer patients with one or two positive sentinel nodes did not compromise overall survival nor regional disease control in these trials. Hence, either excluding or identifying extensive axillary nodal involvement becomes increasingly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…[43][44][45] Furthermore, some studies have raised doubts regarding whether PET/CT could accurately identify the axillary status. 11,12 Combined with the results of our current analysis, further prospective studies are needed to reach a definitive conclusion using unified inclusion and exclusion criteria.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…[43][44][45] Furthermore, some studies have raised doubts regarding whether PET/CT could accurately identify the axillary status. 11,12 Combined with the results of our current analysis, further prospective studies are needed to reach a definitive conclusion using unified inclusion and exclusion criteria.…”
Section: Discussionmentioning
confidence: 84%
“…Upon meta‐regression analysis, the included studies using SUV max as a separate index, the pooled sensitivity increased slightly and specificity decreased significantly ( P = 0.90 and P < 0.05, respectively), which was a little different from the result of Chung et al 45 Many other factors have been reported to affect the accuracy of PET/CT, such as estrogen receptor positivity, lymph node size, and the histopathological procedure used (eg, whether micrometastasis was taken as a positive or negative result) 43–45 . Furthermore, some studies have raised doubts regarding whether PET/CT could accurately identify the axillary status 11,12 . Combined with the results of our current analysis, further prospective studies are needed to reach a definitive conclusion using unified inclusion and exclusion criteria.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Many 18 F-FDG PET or PET/CT studies have also shown promising results for ALN evaluation. It has been reported that the speci city of 18 F-FDG for detecting metastatic ALN is up to 90-100%, but the sensitivity is relatively low to 50-80% (7)(8)(9). Accordingly, 18 F-FDG PET or PET/CT may underestimate the number of metastatic ALN.…”
Section: Introductionmentioning
confidence: 99%